2016
DOI: 10.14791/btrt.2016.4.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Hemangiopericytoma of the Cerebellopontine Angle: A Wolf in Sheep's Clothing

Abstract: Primary meningeal hemangiopericytoma (HPC) is a rare, aggressive dura based tumor that remarkably mimics a meningioma clinically and radiologically. Its occurrence within the cerebellopontine angle (CPA) is exceptional, and establishing the exact diagnosis is of the utmost importance since total resection remains the cornerstone of treatment. A 42-year-old man presented with a three-month history of progressively worsening vertigo and difficulty in walking. On admission, his neurological examination revealed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…It is characterized by paralysis affecting the face and the abducent nerve on the side of the lesion and central hemiplegia on the opposite side[1]. It has been reported that MGS could be found in patients with brainstem tumor such as cavernous angioma[2-4], rimary meningeal hemangiopericytoma[5], neurocysticercosis[6]. As far as we know, only five cases of MGS caused by cerebral infarction have been reported[1,7-10].…”
Section: Introductionmentioning
confidence: 99%
“…It is characterized by paralysis affecting the face and the abducent nerve on the side of the lesion and central hemiplegia on the opposite side[1]. It has been reported that MGS could be found in patients with brainstem tumor such as cavernous angioma[2-4], rimary meningeal hemangiopericytoma[5], neurocysticercosis[6]. As far as we know, only five cases of MGS caused by cerebral infarction have been reported[1,7-10].…”
Section: Introductionmentioning
confidence: 99%
“…They can cause symptoms due to the mass effect or local edema, with compression of the adjacent cerebral parenchyma and increased intracranial pressure. In this way, they usually experience symptoms such as headaches, focal neurological deficits, or comitial seizures [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%